(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2020)
Phosphodiesterases (PDE) are group of enzymes which catalyze the hydrolysis of cAMP and cGMP. Since these cyclic phosphate moieties worked as intracellular second messengers in numerous physiological processes, their inhibition can affect normal physiology of living system. NSAIDs are among the frequently prescribed medications, because of their efficacy as analgesic, antipyretic and anti-inflammatory agents. They are known to block cyclooxygenase pathway. In limited data NSAIDs has been shown anti-tumor potential, and phosphodiesterase inhibition has assumed to be one of the mechanism. To date no further evaluation being done. Further, NSAIDs are classified as cyclooxygenase inhibitors and phosphodiesterase inhibition can imprint its side effects. This study first time investigates the effects of NSAIDs on phosphodiesterase 1 inhibition. The activity against snake venom phosphodiesterase 1 was assayed on a microtitre plate reader spectrophotometer. Selective COX-2 inhibitor, celecoxib, exhibited a potent PDE1 inhibitory activity, at therapeutic doses, with an IC50 value of 29.4 µM. The findings of our study are indicative of new pharmacological actions of cyclooxygenase inhibitors. This article presents the PDE inhibitory properties as a new effects of already existing drugs. These additional effects could be potentially helpful for researchers to assess other physiological and pathological states.